(untitled) (El-Wahat Journal for Research and Studies, 2020)
This Study Aims To Identify The Adoption Of Green Marketing In Industrial Establishments In Algeria Anditsimpactonmarketingperformance.We Presentedaconceptualframeworkforgreenmarketingandmarketingperformance, To Clarifytherelationshipbetweenthetwovariables.We Providedastudyforacompanyspecializedintheproductionofrenewableenergies, Where Weconcludedafterstudyingthedata, That We Accepted Thehypothesesofthestudy, Which Initsentiretystatesthattheadoption Ofgreenmarketingbythealgerian Industrial Establishmentspositivelyaffect Inmarketingperformance. Key Words- Greenmarketing , Marketing Performance , Profitability Sales Volume , Market Share.